2003
DOI: 10.1007/s000110300067
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of hyperalgesia by kinin receptor antagonists or kininogen deficiency in chronic constriction nerve injury in rats

Abstract: These data suggests that kinin were at least partly involved in yielding nociceptor hypersensitivity up to day 14 after CCI. Bradykinin and its B1 and B2 receptors were involved in the maintenance of hyperalgesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 32 publications
4
27
0
Order By: Relevance
“…Increased levels of B 1 and B 2 receptor mRNA or protein have been found in dorsal root ganglia (DRGs) after sciatic nerve constriction in rats and mice (Petersen et al, 1998;Eckert et al, 1999;Levy and Zochodne, 2000;Yamaguchi-Sase et al, 2003;Rashid et al, 2004). Of note, the systemic administration of B 1 or B 2 receptor antagonists has been found to reduce thermal hyperalgesia and mechanical allodynia produced by sciatic nerve constriction in rats (Levy and Zochodne, 2000;Yamaguchi-Sase et al, 2003;Gougat et al, 2004). Plasma seems to be the main source of endogenous kinins after nerve injury, and there is recent evidence demonstrated that neuropathic pain is reduced in mutant plasma kininogen-deficient B/N-Katholiek rats when compared with normal B/N-Kitasato rats (Yamaguchi-Sase et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Increased levels of B 1 and B 2 receptor mRNA or protein have been found in dorsal root ganglia (DRGs) after sciatic nerve constriction in rats and mice (Petersen et al, 1998;Eckert et al, 1999;Levy and Zochodne, 2000;Yamaguchi-Sase et al, 2003;Rashid et al, 2004). Of note, the systemic administration of B 1 or B 2 receptor antagonists has been found to reduce thermal hyperalgesia and mechanical allodynia produced by sciatic nerve constriction in rats (Levy and Zochodne, 2000;Yamaguchi-Sase et al, 2003;Gougat et al, 2004). Plasma seems to be the main source of endogenous kinins after nerve injury, and there is recent evidence demonstrated that neuropathic pain is reduced in mutant plasma kininogen-deficient B/N-Katholiek rats when compared with normal B/N-Kitasato rats (Yamaguchi-Sase et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Of note, the systemic administration of B 1 or B 2 receptor antagonists has been found to reduce thermal hyperalgesia and mechanical allodynia produced by sciatic nerve constriction in rats (Levy and Zochodne, 2000;Yamaguchi-Sase et al, 2003;Gougat et al, 2004). Plasma seems to be the main source of endogenous kinins after nerve injury, and there is recent evidence demonstrated that neuropathic pain is reduced in mutant plasma kininogen-deficient B/N-Katholiek rats when compared with normal B/N-Kitasato rats (Yamaguchi-Sase et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it is unknown whether endogenous bradykinin is involved in the development and/or maintenance of neuropathic pain, its release from injured tissue site as well as the inhibition of neuropathic hyperalgesia by its receptor blockade (Levy and Zochodne, 2000;Yamaguchi-Sase et al, 2003) indicate its role in neuropathic pain following nerve injury. In this report, we showed that exogenous application of very low doses of BK at the peripheral nerve endings in mice produced potent nociceptive flexion response, and these responses were sensitized after peripheral nerve injury.…”
Section: Discussionmentioning
confidence: 99%
“…This increase included a de novo expression of B 1 receptors and an enhancement of the density of preexisting B 2 receptors, and it was accompanied by an increase in the number of bradykinin binding sites on individual neurons. Chronic constriction injury (CCI) to the rat sciatic nerve led to similar changes: an increased B 2 receptor mRNA expression on day 2 and a marked increase in preexisting B 1 receptor mRNA expression 14 day after surgery (428,784). Following crush injury of the sciatic nerve in mice, B 2 receptor mRNA level was elevated in DRG neurons peaking on day 7, and this upregulation was due to an increase in the mRNA content of the neurons (412).…”
Section: Role Of Bradykinin Receptors In Neuropathic Hyperalgesiamentioning
confidence: 95%